REPRESENTATION OF SOCIAL CLASSS IN THE SHORT STORY THE NECKLACE - Alia, Regina Putri; Nurholis, Nurholis (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
The objective of this study is to examine Guy de Maupassant's short story,"The Necklace." This study applies Karl Marx's literary sociology theory along with aqualitative descriptive methodology. One method of data analysis used in this study isreading short stories and marking specific passages that discuss social elements. 2)choosing and identifying narrative elements that depict socioeconomic classes 3)explaining quotes in light of the applied theory 4) drawing recommendations andconclusions from the analysis's findings.